Respuesta :

Answer:

n=-7

Step-by-step explanation:

-3(n+5)=6

-3n-15=6

-3n=21

n=-7

Answer:

n=-7

Step-by-step explanation:

To find n, we need to get n by itself.

−3(n + 5) = 6

-3 and n+5 are being multiplied. To undo this, divide both sides by -3

−3(n + 5)/-3= 6/-3

n+5= -2

5 is being added to n. To undo this, subtract 5 from both sides

n+5-5= -2-5

n= -7

Let's check if -7 is correct. Substitute -7 in for n

-3(-7+5)=6

Add inside the parentheses

-3(-2)=6

Multiply

6=6

So, n=-7 is correct